If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9(11 + -1x) = 3(3k + -9) (11 * 9 + -1x * 9) = 3(3k + -9) (99 + -9x) = 3(3k + -9) Reorder the terms: 99 + -9x = 3(-9 + 3k) 99 + -9x = (-9 * 3 + 3k * 3) 99 + -9x = (-27 + 9k) Solving 99 + -9x = -27 + 9k Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-99' to each side of the equation. 99 + -99 + -9x = -27 + -99 + 9k Combine like terms: 99 + -99 = 0 0 + -9x = -27 + -99 + 9k -9x = -27 + -99 + 9k Combine like terms: -27 + -99 = -126 -9x = -126 + 9k Divide each side by '-9'. x = 14 + -1k Simplifying x = 14 + -1k
| 6b-4(4+b)=-1+7b | | -19+74=-5x-15 | | 7-6t-5t^2=0 | | 4x-3=3x+6y | | 26+2x=-7x+7(x+2) | | 10x+32x+12= | | -5t=-13-2t | | 4x-11=(-4) | | 6m^2-17m+12=0 | | -3(x+2+x+2)-4=-112 | | 2n+6=-8 | | x^2-49=x-1 | | (5/2x+1/4x)=5/4+x | | x-7=rad(x-1) | | 5.2=k-3.7 | | T=C+l+G | | 25/5(2+3) | | K-9-(2+k)=m | | (x-7)2=81 | | 7x-8=-x+8 | | -4+2x= | | b/4-1=-7 | | 8/36+4/9 | | 3/4n=-15 | | 2x^2-3y^2=-19 | | 36p^2+4=20 | | 3/8=x/20 | | X^2-2=-1 | | 4/x=9/5-7x-4/5x | | 3(2x)=96 | | -4x-12= | | N^2-4=77 |